IDENTIFIKASI ASAM AMINO IKAN LAYANG (Decapterus russelli) PADA LOKASI PENANGKAPAN BERBEDA - Eko Cahyono; Indra Mardani (Fakultas Pertanian Universitas Alkhairaat Palu, 2020)
Decapterus ruselli are a fisheries resource caught in the waters of Teluk Tomini and the Selat Makassar and have high economic value. The purpose of the study was to find out the profile of Decapterus ruselli fatty acids being caught at different locations. Methods used in this research is descriptive analysis. Results from this study indicate that plankton's abundance, weight in fish, protein levels, and amino acids in the waters of Teluk Tomini are higher than the Selat Makassar.